Development of a Flexible, Light Weight Structure, Adaptable to any Space through a Shape Shifting Feature. (2016) - Cunha, Fenando; Mota, Carlos; Reis, Ana; Marques, Paulo; Pinto, Rui; Fangueiro, Raul
Abstract: Life form structure (LFS) is an architectural system with the ability to change its shape according to the environment conditions. The shape can be altered by expansion, shrinkage, or twisting of the structure. This gives the perception of three-dimensional transformation. The system shapes can be altered quickly into a new one, which is functionally attractive and adaptable, according to the need and functions that arise in the course of time. To achieve the desired effect, it is necessary to use lightweight materials with good flexibility. Architectural membrane will be the right choice for this type of application. The multilayer structure with a total thickness of around 6 mm, consists of rigid PVC plates in the interior, bonded to a PVC coated high tenacity polyester membrane. The membrane act as a connecting element between the rigid PVC elements. In this way, the outer layer of the architectural system is continuous and the interior will be discontinuous, enabling them to create a geometric matrix, which has features of structural shape shifting. It is a novel kind of architectural system that possess very good flexibility in all direction along with attractive aesthetic outlook. The system offers protection against all types of environmental conditions (rain, wind, sunlight, etc.) and can be useful for both indoor (attractive space for exhibition) and outdoor applications (beach tent, tent for stall, etc.).